FDI in Tourism Sector and Economic Growth in Sumatra Utara - Simatupang, Parhimpunan; Chik, Abdul Razak (Journal the Winners: Economics, Business, Management, and Information System Journal, 2014)
Globalization and neo liberal policies such as liberalization and privatization have generated a significant growth for FDI and considered an important source for capital and foreign currency, capable of spurring economic growth in developing countries. One sector that received particular attention, due to its significant contributions towards economic development, especially in Indonesia, is tourism. Tourism investments in Indonesia are mainly focused on the development of fully-integrated resort sites that help boost the construction of tourist facilities such as hotels and the development of the surrounding environment through social and cultural aspects. The total contribution of travel and tourism to GDP was IDR736.3 billion or 8.9% of GDP in 2012. Foreign direct tourism investments grew by 210% between 2011 and 2012, or at an annual compound average growth rate of 38% between 2006 and 2012. While the implications are at national level, not much could be gathered on the local perspectives. This paper intends to explore the implication of FDI in tourism sector towards economic growth in one of tourism attraction provinces in Indonesia—Sumatra Utara. Specifically, which economic factors contributed towards FDI inflows and their impacts on economic growth in Sumatra Utara.